2020
DOI: 10.3390/su12072630
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing and Reporting Practice Errors by Nurses in Residential Long-Term Care Settings: A Systematic Review

Abstract: Patient safety is crucial for the sustainability of the healthcare system. However, this may be jeopardized by the high prevalence of practice errors, particularly in residential long-term care. Development of improvement initiatives depends on full reporting and disclosure of practice errors. This systematic review aimed to understand factors that influence disclosing and reporting practice errors by nurses in residential long-term care settings. A systematic review using an integrative design was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…A previous systematic review in 2016 included a majority of studies conducted in western countries (Vrbnjak et al, 2016), also confirming the findings of this review, while a global study on error reporting systems and barriers in 16 different countries from Africa, Australia, Europe, and North America showed a major commonality between perceived barriers to incident reporting (Holmström et al, 2012). Furthermore, a review in primary care identified that there is a lack of safety culture (Lainer et al, 2015) while studies supported partially the findings of this review both in primary care (Michel et al, 2017) and in long term care settings (Vaismoradi et al, 2020).…”
Section: Limitations Of the Reviewsupporting
confidence: 85%
“…A previous systematic review in 2016 included a majority of studies conducted in western countries (Vrbnjak et al, 2016), also confirming the findings of this review, while a global study on error reporting systems and barriers in 16 different countries from Africa, Australia, Europe, and North America showed a major commonality between perceived barriers to incident reporting (Holmström et al, 2012). Furthermore, a review in primary care identified that there is a lack of safety culture (Lainer et al, 2015) while studies supported partially the findings of this review both in primary care (Michel et al, 2017) and in long term care settings (Vaismoradi et al, 2020).…”
Section: Limitations Of the Reviewsupporting
confidence: 85%
“…Collaboration through communication, sharing information and the provision of regular feedback can improve adherence to the principles of safe medication practice [ 39 ]. Nurses have the required knowledge and skills regarding medicines management and spend more time with patients than physicians and pharmacists, increasing their chances of detecting medicines discrepancies and near misses [ 67 , 68 , 69 ]. Therefore, nurses’ role, accountability and knowledge of medications should be taken into account when strategies are devised to improve medicines management [ 19 , 66 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the majority of ADRs and other medicine-related harms arise from poor monitoring rather than errors in prescribing [ 32 , 33 , 40 , 41 , 42 , 43 ], being primarily dose-related [ 44 ]. The situation can be greatly improved by enhanced monitoring and reporting [ 18 , 19 , 47 ]. ADRe was developed from earlier research on nurse-led medication checking, originally in relation to mental health medicines prescribed for clients of community mental health teams [ 48 , 49 , 50 ].…”
Section: Adre and Systematic Medicines Management As A Route To Efmentioning
confidence: 99%